Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x=\frac{2019^{2020}+1}{2019^{2019}+1}>\frac{2019^{2020}+1+2018}{2019^{2019}+1+2018}=\frac{2019^{2020}+2019}{2019^{2019}+2019}=\frac{2019\left(2019^{2019}+1\right)}{2019\left(2019^{2018}+1\right)}=\frac{2019^{2019}+1}{2019^{2018}+1}\)(1)
\(y=\frac{2019^{2019}+2020}{2019^{2018}+2020}< \frac{2019^{2019}+2020-2019}{2019^{2018}+2020-2019}=\frac{2019^{2019}+1}{2019^{2018}+1}\left(2\right)\)
Từ (1) và (2) \(\Rightarrow x>y\)
\(f\left(x\right)=ax^{2\: }+bx+c\)
\(\Rightarrow f\left(1\right)=a\cdot1^2+b\cdot1+c=a+b+c\)
Ta có: \(\hept{\begin{cases}a+3c=2019\\a+2b=2020\end{cases}}\)
\(\Rightarrow a+3c+a+2b=2019+2020\)
\(\Leftrightarrow2a+2b+3c=4039\)
\(\Leftrightarrow2\left(a+b+c\right)+c=4039\)
Vì a,b,c không âm => 2(a+b+c)\(\le2\left(a+b+c\right)+c=4039\)
\(\Leftrightarrow2\left(a+b+c\right)=4039\)
\(\Leftrightarrow a+b+c=\frac{4039}{2}\)
\(\Leftrightarrow a+b+c=2019\frac{1}{2}\)
\(\Rightarrow f\left(1\right)\le2019\frac{1}{2}\left(đpcm\right)\)
\(x=2019\)\(\Rightarrow x+1=2020\)
\(\Rightarrow B=x^{2019}-\left(x+1\right).x^{2018}+........-\left(x+1\right).x^2+\left(x+1\right).x+1\)
\(=x^{2019}-x^{2019}+x^{2018}+.......-x^3-x^2+x^2+x+1\)
\(=x+1=2020\)
Vậy tại \(x=2019\)thì \(B=2020\)
Ta có x=2019
=> x + 1=2020
thay x+1 vào B, ta có:
\(A=x^{2019}-\left(x+1\right)x^{2018}+\left(x+1\right)x^{2017}-...+\left(x+1\right)x-1\)
=> \(A=x^{2019}-x^{2019}-x^{2018}+x^{2018}+x^{2017}-...+x^2+x-1\)
=> \(A=x-1=2020-1=2019\)
a) Ta có:\(8\left(x-2019\right)^2⋮8\Rightarrow25-y^2⋮8\)\(\left(1\right)\)
Mặt khác: \(8\left(x-2019\right)^2\ge0\Rightarrow25-y^2\ge0\)\(\left(2\right)\)
Từ\(\left(1\right),\left(2\right)\)ta có: \(y^2=1;9;25\)
Xét:\(y^2=1\Rightarrow8\left(x-2019\right)^2=24\Rightarrow\left(x-2019\right)^2=3\left(ktm\right)\)
\(y^2=9\Rightarrow8\left(x-2019\right)^2=16\Rightarrow\left(x-2019\right)^2=2\left(ktm\right)\)
\(y^2=25\Rightarrow8\left(x-2019\right)^2=0\Rightarrow\left(x-2019\right)^2=0\Rightarrow x-2019=0\Rightarrow x=2019\left(tm\right)\)
Vậy \(y=5;x=2019\)
\(y=-5;x=2019\)